PENGARUH FAKTOR FUNDAMENTAL MAKRO DAN MIKRO TERHADAP RETURN SAHAM - Nur Ismanidar (Jurnal Investasi Islam, 2017)
The aim of this study to find the effect of macro fundamental factors, namely inflation and interest rates of SBIs, and micro fundamentals in the form of financial ratios as measured by Return On Assets (ROA) and Earning Per Share (EPS) on stock returns in Indonesia capital market. The research object is Mining Company which listed in Indonesia Stock Exchange since 2009-2012. The sample selection procedure is purposive sampling. In this research, Multiple Linear Regression method of Generalized Least Squares (GLS) method with fixed effects approach through Chow Test and Hausman Test is done. Hypothesis test used t-statistic and f-statistic test with 5% significance. The results showed that the independent variables affect the stock return with a significance value of F by 0.000%. Partially variable of inflation rate has a positive relationship to stock returns indicating that the inflation was caused by the monetary sector. On the other hand, variable Return on Assets (ROA) has a negative relationship indicating that a good Return on Assets (ROA) does not encourage the increase of stock prices, and proved that the variable Earning Per Share (EPS) has a positive effect on stock returns indicating that the greater Earning Per Share (EPS) will increase the acquisition of stock returns.